Pengaruh Teknik Penanakan Beras Terhadap Evaluasi Sensori dan Tingkat Kepulenan Nasi Dari Beras Analog Berbahan Baku Tepung Sorgum, Mocaf, Glukomanan, dan Kelor: The Effect of Rice Cooking Techniques on the Sensory Evaluation Test and Fluffiness Levels of Analog Rice Made From Sorghum, Mocaf, Glucomannan, and Moringa Flour - Sailendra, Nova Veronika; Aji, Arif Sabta; Saloko, Satrijo; Aprilia, Veriani; Djidin, Radhiyya Tsabitah; Rahmawati, Sri; Khoirunnisah, Frisqi Meilany (Universitas Airlangga, 2024)
Background: Rice cooking is the process of rice making with several cooking stages and types such as using rice cookers and steamers. This analog rice innovation aims to increase the nutritional value, food diversification, and functional foods. Objectives: To determine the effect of rice cooking techniques on sensory tests (color, texture, aroma, and overall appearance) and fluffiness levels between analog rice and C4 rice. Methods: This experimental research used a Completely Randomized Design (CRD) on analog rice resulting from the best treatment (P2) with an additional composition of 2 gram of Moringa flour. The cooking techniques used rice cookers and steamers for cooking both analog rice and C4 rice. A total of 25 semi-trained panelists were selected to identify sensory evaluation and the fluffiness levels of the product. The statistical analysis used the Mann-Whitney test with the help of SPSS version 23.0. Results: Cooking techniques using a rice cooker and a steamer influenced the sensory evaluation tests (color (p=0.004), texture (p=0.002), and overall appearance (p=0.006)) and fluffiness levels (p=0.004) for analog rice. However, cooking techniques did not influence the sensory evaluation test for taste (p=0.396) and aroma (p=0.058). The sensory tests such as color (p=0.607), texture (p=0.578), overall appearance (p=0.701), taste (p=0.482) and aroma (p=0.216) and the level of fluffiness in C4 rice (p=0.891) did not show differences. Conclusions: The steaming cooking technique influences the preference and fluffiness levels of analog rice. Cooking analog rice with the steaming technique is highly recommended in order to increase consumer preference.